2005
DOI: 10.1002/isaf.261
|View full text |Cite
|
Sign up to set email alerts
|

Modelling small‐business credit scoring by using logistic regression, neural networks and decision trees

Abstract: Previous research on credit scoring that used statistical and intelligent methods was mostly focused on commercial and consumer lending. The main purpose of this paper is to extract important features for credit scoring in small‐business lending on a dataset with specific transitional economic conditions using a relatively small dataset. To do this, we compare the accuracy of the best models extracted by different methodologies, such as logistic regression, neural networks (NNs), and CART decision trees. Four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(44 citation statements)
references
References 14 publications
0
38
0
Order By: Relevance
“…Each node in the tree specifies a test of some attribute of the instance and each branch descending from that node corresponds to one of the possible values for this attribute [16]. Advantages of using decision learning tree algorithms are: 1) They generalize in a better way for unobserved instances, once examined the attribute value pair in the training data.…”
Section: Decision Tree Modelmentioning
confidence: 99%
“…Each node in the tree specifies a test of some attribute of the instance and each branch descending from that node corresponds to one of the possible values for this attribute [16]. Advantages of using decision learning tree algorithms are: 1) They generalize in a better way for unobserved instances, once examined the attribute value pair in the training data.…”
Section: Decision Tree Modelmentioning
confidence: 99%
“…Baesens et al [3] showed that the support vector machines achieve the highest accuracy rate, while the neural networks perform the best in terms of the area under the ROC curve. Bensic et al [4] suggested that the accuracy of probabilistic neural network is superior to that of logistic regression, CART decision trees, radial basis function, multi-layer perceptron and learning vector quantization. Antonakis and Sfakianakis [2] evaluated the performance of k-nearest neighbors decision rule, multi-layer perceptron, decision trees, logistic regression, linear discriminant analysis and naïve Bayes, showing that the k-nearest neighbors rule achieved the highest accuracy and the neural network was the best method in terms of the Gini coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…The performance of the LVQ will be compared to the performance of the probabilistic neural network (PNN) due to its effectiveness in financial classification problems (Schierholt & Dagli, 1996;Prokhorov & Wunsch, 1995, 1998Bensic et al, 2005;Mehrara et al, 2010). However, to the best of our knowledge the LVQ neural network has not been used for stock market modelling and forecasting.…”
Section: Introductionmentioning
confidence: 99%